Paradoxes du stigmate : les représentations médiatiques de Marine Le Pen - Frédérique Matonti (Genre, Sexualité et Société)
Media representations of female politicians differ from those of men involved in politics. For example, they currenly disadvantage women by linking them to the gender roles of daughter, spouse and mother, invoking skills far removed from the political ones expected. But, in fact, these media representations are giving an advantage to Marine Le Pen over her father, the former Front National leader, Jean-Marie Le Pen. This article attempts to explain why.